The Efl Teachers’ Challenges in Teaching Speaking Online: A Case Study - Lenny Marzulina; Dian Erlina; Herizal Herizal; Lily Kurnia Margaretta (Edukasi, 2022)
This article presents English teacher's challenges in teaching speaking online at one Madrasah Tsanawiyah (MTs) in Palembang, South Sumatera, Indonesia. A qualitative case study was employed in conducting this research. Data were collected by using semi-structured interview with the English teacher through a set of open-ended questions. Thematic analysis was used to identify, analyze, and describe the obtained data in the process of selecting codes and constructing themes. The results revealed that the teacher faced some main challenges in teaching speaking online, as follows: (a) lack of students’ confidence in speaking English, (b) internet connection issues, (c) lack of students’ learning interactions and participations, (d) difficulty in designing/developing speaking materials for online class, (e) difficulty in managing the time, and (f) unreliable online teaching and learning devices. These challenges should be considered and anticipated by the teachers and other pertinent parties to get the alternatives for solutions.